Expression of TRPC6 in Renal Cortex and Hippocampus of Mouse during Postnatal Development - Xu, Pengjuan (Public Library of Science, 2012)
TRPC6, a member of the TRPC family, attracts much attention from the public because of its relationship with the disease. In both the brain and kidney, TRPC6 serves a variety of functions. The aim of the present study was to observe the expression and effects of TRPC6 in renal cortex and hippocampus during early postnatal development of the mouse. In the present study, immunohistochemistry and Western blotting were used to detect the expression of TRPC6 in the mouse kidney and hippocampus of postnatal day 1, 3, 5, 7, 14, 21, 28 and 49 (P1, P3, P5, P7, P14, P21, P28 and P49). Results showed that the expression of TRPC6 was increased in the mouse hippocampus, and there was a significant increase between P7 and P14 during the postnatal development. Meanwhile, the expression of TRPC6 was also detected in glomerulus and tubules, and a decreased expression was found during postnatal maturation of mouse renal cortex. From these in vivo experiments, we concluded that the expression of TRPC6 was active in the developing mouse kidney cortex, and followed a loss of expression with the development of kidney. Meanwhile, an increased expression was found in the hippocampus with the development. Together, these data suggested that the developmental changes in TRPC6 expression might be required for proper postnatal kidney cortex development, and played a critical role in the hippocampus during development, which formed the basis for understanding the nephrogenesis and neurogenesis in mice and provided a practically useful knowledge to the clinical and related research.